Water Stewardship (2020)
Achieving true wholesome sustainability requires a change of heart. Hence this book starts in the heart. It asks the timely question of ‘how do we become true water stewards?’ The transformation to a new sustainable practice will be made through a new connection with our heart, a more holistic type of analysis (brains) and the right actions based on personal integrity (hand). A water steward should be similar to the shepherds of olden days. They were given the responsibility to guard the sheep. The village trusted they would take care of the herd, make sure it would be well fed, protected from storms and kept together. The shepherd learned to take a long term perspective for the herd, ensuring that the pastures were not overgrazed, that the herd was not led too far away from access to water and that shelter was in reach in the event of storms and dangerous predators. Over time the shepherds became increasingly skilled in caring for the herd. They integrated the responsibility of the well-being of the herd into their identity. In a similar way, we can take the responsibility for human water consumption and our interaction with the natural world. We need to understand and work according to the big picture and the very long term perspective. Being a water steward requires deep reflection of how water should be treated and our relationship with water. Water utility professionals have the knowledge and have been trusted with the role of managing human water consumption. This is a great responsibility and requires deep reflection of how this should be done. The book will present ideas and concepts for the new role as well as questions for personal reflection.